2009
DOI: 10.1098/rsif.2009.0127
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of the morphology and mechanical behaviour of barnacle cyprid footprint proteins at the nanoscale

Abstract: Barnacles are a major biofouler of man-made underwater structures. Prior to settlement, cypris larvae explore surfaces by reversible attachment effected by a 'temporary adhesive'. During this exploratory behaviour, cyprids deposit proteinaceous 'footprints' of a putatively adhesive material. In this study, footprints deposited by Balanus amphitrite cyprids were probed by atomic force microscopy (AFM) in artificial sea water (ASW) on silane-modified glass surfaces. AFM images obtained in air yielded better reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
3
24
0
Order By: Relevance
“…This walking is called 'exploring behavior', aiming to decide whether the substrate is suitable for settling [14,15]. After the exploring behavior, a cypris attaches firmly and permanently to the substrate by secreting the adhesive proteins [16,17] and then transforms into a juvenile. In the post-settlement stage, barnacles secrete cement proteins to the substrate and broaden their adhesion area [18].…”
Section: Barnaclesmentioning
confidence: 99%
“…This walking is called 'exploring behavior', aiming to decide whether the substrate is suitable for settling [14,15]. After the exploring behavior, a cypris attaches firmly and permanently to the substrate by secreting the adhesive proteins [16,17] and then transforms into a juvenile. In the post-settlement stage, barnacles secrete cement proteins to the substrate and broaden their adhesion area [18].…”
Section: Barnaclesmentioning
confidence: 99%
“…Previous work on different fouling deposits and surfaces have used atomic force microscopy (AFM) to study surfaces, such as Parbhu et al ,(2006) Santos et al (2004, Verran and Whitehead (2006) and Whitehead et al (2006). AFM is able both to measure surface topography and energetics over a nanometre to micron scale (such as in marine biofilms by Phang et al, 2006Phang et al, , 2010 However there is very little work done in which AFM has been used to study food fouling problems.…”
Section: Introductionmentioning
confidence: 99%
“…Phang et al [20] used atomic force microscopy (AFM) to characterise nanoscopically the mechanical behaviour of this material, reporting an absence of strain-rate dependence in the force required to rupture protein aggregates, therefore implying viscous, rather than viscoelastic character for subunits of the footprint material. However, caution must always be exercised when extrapolating such data to the whole-organism and it is clear that in its natural application the footprint material is highly elastic and not simply viscous (Movie S10).…”
Section: Resultsmentioning
confidence: 99%
“…However, caution must always be exercised when extrapolating such data to the whole-organism and it is clear that in its natural application the footprint material is highly elastic and not simply viscous (Movie S10). In fact, when testing droplets of spider adhesive, Sahni et al [35] only observed viscoelastic character at strain rates above 10 µm/second, whereas Phang et al [20] performed experiments between 0.5 and 11 µm/second. It is perhaps not surprising, therefore, that only a gradual increase in rupture force was observed in the range of strain rates tested by Phang et al [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation